Review paper Allergy to orthopaedic metallic implants - Dąbrowska, Danuta; Roszkiewicz, Jadwiga; Sosnowski, Grzegorz; Wójcik, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Today, due to increasing lifespan, the significance and range of orthopaedics is increasing. Orthopaedic surgeons are increasingly using metallic implants, particularly for younger patients. Some patients have orthopaedic and dermatological complications caused by sensitivity to metals included in metallic implants. Allergy to metals in patients with metallic implants has been discussed for a long time by many specialists. In the 1970s growth and exacerbation of contact dermatitis especially nickel allergy caused by metallic implants (plates, screws, nails, prostheses), were noticed. Orthopaedic complications such as delayed or non-union of fractured bone and prosthesis loosening were linked with implant-related sensitivity. This problem has remained unresolved so far.